A TGA Investigation to Co‐Pyrolysis Characteristics of Shenhua Direct Coal Liquefaction Residue and Huolinhe Lignite and the CO2 Gasification Behavior of the Derived Char. Issue 39 (16th October 2020) - Fan, Tao; Qu, Yang; Chang, Zhibing; Zhou, Lingmei; Hao, Yan; Liu, Shuai; Chu, Mo
Abstract: Co‐pyrolysis of direct coal liquefaction residue (DCLR) and low rank coals was regarded as reliable and efficient method to process DCLR. The treatment of the derived co‐pyrolysis char is important for the comprehensive utilization of DCLR. In this study, the non‐isothermal co‐pyrolysis of Shenhua DCLR and Huolinhe lignite, and the isothermal CO2 gasification of the co‐pyrolysis char were performed by the thermogravimetric analysis method. The interactive effect of co‐pyrolysis and the CO2 gasification behavior of the derived char were explored by comparing the experimental and calculated thermogravimetric/derivative thermogravimetric (TG/DTG) curves and reactivity – conversion ( R ‐ x ) curves, respectively. The results show that the devolatilization pattern at 200–600 °C was modified and part of volatiles were released in advance. As the experimental co‐pyrolysis T max was lower by 7–13 °C than the calculated value, while it was almost equal to the T max of lignite pyrolysis. We tentatively concluded that lignite devolatilization could promote the evaporation of molten components of DCLR. Moreover, DCLR and lignite could polymerize or condensation with each other at 650–900 °C. The lignite char within co‐pyrolysis char could support the char skeleton and hold a high porosity. Therefore, the CO2 gasification reactivity of co‐pyroysis char was promoted and the experimental reactivity exceeded the calculated value over the conversion range of 12–90 %. Abstract : During co‐pyrolysis of Shenhua direct coal liquefaction residue and Huolinhe lignite, they could polymerize or condensate with each other at 650–900 °C, which lead to extra volatile release and to the liberation of massive amounts of heat. The lignite char within co‐pyrolysis char could support the char skeleton and retain a high porosity. This is conducive to the mass transfer process of CO2 gasification, and thereby increased the gasification reactivity of co‐pyroysis char.